If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + -6 + -6 = 0 Reorder the terms: -6 + -6 + 7x = 0 Combine like terms: -6 + -6 = -12 -12 + 7x = 0 Solving -12 + 7x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '12' to each side of the equation. -12 + 12 + 7x = 0 + 12 Combine like terms: -12 + 12 = 0 0 + 7x = 0 + 12 7x = 0 + 12 Combine like terms: 0 + 12 = 12 7x = 12 Divide each side by '7'. x = 1.714285714 Simplifying x = 1.714285714
| 9x-8-8=0 | | 28+34-2x=458 | | 2x^4+8x^2-90=0 | | -5x+7=-9 | | 8x^4+26x^2+6=0 | | 2x+12=x+8 | | 2x^4-2x^2-24=0 | | 6x-17=4-x | | 8x-15=3-x | | (17b-2)-4(4b+4)=-7 | | (7b-2)-4(4b+4)=-7 | | 9x+4x+4+9=4x+3+8x | | -.25(x-8)+.5(x+2)=x+6 | | 10=4y-2y | | -5a-9=21 | | -.17(x-18)+6(.5)(x+2)=6(x+8) | | -.16666(x-18)+6(.5)(x+2)=6(x+8) | | 6y=-5(y+1) | | 12+(2-40)-6= | | 5x-5y=10 | | 2a^2-5=0 | | 3z-4=3z+2 | | -20y=da | | a+198=2(x+7)(x-3) | | 2x^4-16x^2+30=0 | | a+120=2(x+7)(x-3) | | -5x^2+9x+2=0 | | 5x-2=26-2x | | -18=-2n | | 6(2-t)-(3-4t)=4 | | 5(x+8)=2(x+6) | | 5(x-8)=2(x+6) |